A Cytokine-like Protein DKK3 Is Atheroprotective - Yu, Baoqi; Kiechl, Stefan; Qi, Dan; Wang, Xiaocong; Song, Yanting; Weger, Siegfried; Mayr, Agnes; Le Bras, Alexandra; Karamariti, Eirini; Zhang, Zhongyi; del Barco Barrantes, Ivan; Niehrs, Christof; et al. (Circulation, 2017)
Background -Dickkopf-related protein (DKK) 3 is a secreted protein that is involved in the regulation of cardiac remodeling and vascular smooth muscle cell differentiation, but little is known about its role in atherosclerosis. Methods -We tested the hypothesis that DKK3 is atheroprotective using both epidemiological and experimental approaches. Blood DKK3 levels were measured in the Bruneck Study in 2000 (n=684) and then in 2005 (n=574). DKK3-deficient mice were crossed to ApoE(-/-) mice to evaluate atherosclerosis development and vessel injury-induced neointimal formation. Endothelial cell migration and the underlying mechanisms were studied using in vitro cell culture models. Results -In the prospective population-based Bruneck Study, the level of plasma DKK3 was inversely related to carotid artery intima-media thickness and five-year progression of carotid atherosclerosis, independently from standard risk factors for atherosclerosis. Experimentally, we analyzed the area of atherosclerotic lesions, femoral artery injury-induced re-endothelialization and neointima formation in both DKK3(-/-)/ApoE(-/-) and DKK3(+/+)/ApoE(-/-) mice. It was demonstrated that DKK3 deficiency accelerated atherosclerosis and delayed re-endothelialization with consequently exacerbated neointima formation. To explore the underlying mechanisms, we performed transwell and scratch migration assays using cultured human endothelial cells, which exhibited a significant induction in cell migration in response to DKK3 stimulation. This DKK3-induced migration was associated with activation of ROR2 and DVL1, activated Rac1 GTPases and upregulated JNK and c-jun phosphorylation in endothelial cells. Knockdown of ROR2 receptor using specific siRNA or transfection of a dominant negative form of Rac1 in endothelial cells markedly inhibited cell migration and downstream JNK and c-jun phosphorylation. Conclusions -This study provides the evidence for a role of DKK3 in the protection against atherosclerosis involving endothelial migration and repair, with great therapeutic potential implications against atherosclerosis.
EVALuna:34144